Frequency of primary cutaneous lymphoma variants in Austria: retrospective data from a dermatology referral centre between 2006 and 2013. (20th January 2015) - Eder, J.; Kern, A.; Moser, J.; Kitzwögerer, M.; Sedivy, R.; Trautinger, F.
Abstract Background Primary cutaneous lymphomas (PCL) are a heterogenous group of rare lymphoid neoplasms with incomplete information on global and regional prevalence. The recently introduced lymphoma classifications define distinctive clinicopathological disease entities that should allow for more accurate epidemiological assessment. Objective The aim of this study was to evaluate the prevalence and clinical spectrum of PCL diagnosed and treated at the Department of Dermatology and Venereology in St. Pölten, Lower Austria, a dermatology referral centre providing secondary and tertiary care for a population of about 600 000. Methods In this retrospective study pathology reports, electronically archived between 2006 and 2013, were screened for the terms lymphoma, mycosis fungoides (MF) and lymphomatoid papulosis (LyP). Patients were diagnosed according to the current WHO‐EORTC classification for cutaneous lymphomas and results were compared with data from European, US and Asian centres. Results Among 86 patients with PCL (age 58.3 ± 17.35 years, mean ± SD; women 38%, n = 33; men 62%, n = 53) 83% (n = 71) were classified as cutaneous T‐cell lymphomas (CTCL) and 17% (n = 15) as cutaneous B‐cell lymphomas (CBCL). Nine patients with CTCL showed associated haematological disorders and malignomas. Among 47 MF patients following variants were observed: pilotropic MF (n = 2), follicular mucinosis (n = 1), unilesional MF (n = 1), large‐cell transformation (n = 3), erythrodermic MF (n = 1), poikilodermatous MF (n = 2) and posttransplant lymphoproliferative disorder (CD8+ MF with gamma/delta phenotype after renal transplantation) (n = 1). One patient had MF concurrent with lymphomatoid papulosis. The group of CBCL comprised six cases (40%) of PCMZL and PCFCL each, 20% (n = 3) were classified as PCLBCL, LT. Conclusion This study for the first time provides data on the distribution of PCL clinicopathologic variants and stages according to the latest classification and staging systems in an Austrian referral centre.